POLITICAL WILL PEMERINTAH KOTA PEKANBARU DALAM PEMBUATAN SERTIFIKAT TANAH MILIK PEMERINTAH DAERAH TAHUN 2018-2019 - Fajarina, Monica Ananda; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The population growth of Pekanbaru City which continues to increase, makes the need for land increasing day by day. This has led to a lot of expropriation of government-owned land by a group of people. Therefore, it is very necessary to have a desire or Political Will from the Pekanbaru City Government in making Land Assets Certificates Owned by the Regional Government for 2018-2019. The purpose of this research is to find out the Political Will and the obstacles of the Pekanbaru City Government in Making Land Certificates Owned by the Regional Government in 2018-2019. This study uses a qualitative descriptive method, with 5 informants, meanwhile the data collection technique is by using interviews and documentation.This study found that the Political Will of the Pekanbaru City Government in Making Land Certificates Owned by the Regional Government in 2018-2019. This can be seen from 1) Government Initiatives in Making Land Certificates, 2) Policy/Program Options in Making Land Certificates, 3) Mobilization of Parties involved in Making Land Certificates, 4) Public Commitment and Resource Allocation in Making Land Certificates, 5) Sustainability of Government Efforts in Making Land Certificates, 6) Learning and Adapting by the Government in Making Local Government Land Certificates. Meanwhile, the obstacles in this asset management process are: a) Budgetary constraints, b) Land on which there are buildings, c) Lack of Human Resources, d) Administration or inventory that is still lacking by the Regional Financial and Asset Management Agency.Â Keywords: Political Will, Government Asset Management.